A Cooperative Q-Learning Path Planning Algorithm for Origin-Destination Pairs in Urban Road Networks. (7th October 2015) - Zhang, Xiaoyong; Li, Heng; Peng, Jun; Liu, Weirong
Abstract : As an important part of intelligent transportation systems, path planning algorithms have been extensively studied in the literature. Most of existing studies are focused on the global optimization of paths to find the optimal path between Origin-Destination (OD) pairs. However, in urban road networks, the optimal path may not be always available when some unknown emergent events occur on the path. Thus a more practical method is to calculate several suboptimal paths instead of finding only one optimal path. In this paper, a cooperativeQ -learning path planning algorithm is proposed to seek a suboptimal multipath set for OD pairs in urban road networks. The road model is abstracted to the form thatQ -learning can be applied firstly. Then the gray prediction algorithm is combined intoQ -learning to find the suboptimal paths with reliable constraints. Simulation results are provided to show the effectiveness of the proposed algorithm.